THE WAY OF CHILE TO SOCIALISM, SALVADOR ALLENDE FROM THE 50 YEARS OF THE POPULAR UNITY - Roitman Rosenmann, Marcos (2021)
It is the 50th anniversary of the triumph of the Unidad Popular and the Chilean way to socialism. The figure of Salvador Allende was its maximum exponent and defender. The electoral victory on the 4th of September of 1970 marked a milestone in the processes of transition to socialism. It was conceived as a peaceful way because of its respect for institutions, the development of political freedoms, the deepening of social liberties, and the rejection of violence, understood as the insurrectionary seizure of power. The Chilean path was frustrated by the coup d’etat on September 11, 1973.